2021
DOI: 10.1108/bfj-03-2021-0271
|View full text |Cite
|
Sign up to set email alerts
|

Motivations, self-congruity and restaurant innovativeness as antecedents of a creative-food tourism experience: the moderating effect of first-time and repeat tourists

Abstract: PurposeThis study aims to analyze the drivers of a creative food tourism experience (CFTE) and its effect on the tourists' perceived authenticity and satisfaction. Specifically, this study captures the importance to explain a CFTE of two sets of stimuli: internal stimuli, including push motivations for food travel (i.e. emotional, cultural and social) and the tourist self-congruity (i.e. actual and ideal) with the chosen food establishment; and external stimuli, referred to the pull motivation exerted by resta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 72 publications
2
18
0
Order By: Relevance
“…Customer perceptions of restaurant innovativeness can increase value cocreation (Kim et al , 2019; Yen et al , 2020), enhance consumer loyalty (Kim et al , 2021) and business brand equity (Omar et al , 2021). Furthermore, it is the antecedent of a creative food tourism experience (Gómez-Rico et al , 2021). The following subsections develop the hypotheses to interpret the relationship between food tourists’ perceptions of restaurant innovativeness and the destination's cognitive food image.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Customer perceptions of restaurant innovativeness can increase value cocreation (Kim et al , 2019; Yen et al , 2020), enhance consumer loyalty (Kim et al , 2021) and business brand equity (Omar et al , 2021). Furthermore, it is the antecedent of a creative food tourism experience (Gómez-Rico et al , 2021). The following subsections develop the hypotheses to interpret the relationship between food tourists’ perceptions of restaurant innovativeness and the destination's cognitive food image.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This result is consistent with previous studies. For instance, Gómez-Rico et al. (2022) indicated that tourists' creative food experiences are aligned with their self-congruity; the higher the self-congruity, the higher the restaurant experience.…”
Section: Discussionmentioning
confidence: 99%
“…Actual self-image refers to consumers’ true perceptions of themselves and personal identity. Ideal self-image is what consumers aspire to become ( Sirgy, 2018 ; Gómez-Rico et al, 2021 ). It also reflects the attributes a consumer wishes to acquire.…”
Section: Introductionmentioning
confidence: 99%